2020
DOI: 10.3390/ma13245615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intrabony Length and Cortical Bone Density on the Primary Stability of Orthodontic Miniscrews

Abstract: Miniscrews have gained recent popularity as temporary anchorage devices in orthodontic treatments, where failure due to sinus perforations or damage to the neighboring roots have increased. Issues regarding miniscrews in insufficient interradicular space must also be resolved. This study aimed to evaluate the primary stability of miniscrews shorter than 6 mm and their feasibility in artificial bone with densities of 30, 40, and 50 pounds per cubic foot (pcf). The primary stability was evaluated by adjusting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…In this study, the highest buccal and palatal depth is detected between first molar and second molar. Jin et al indicated that regardless of the cortical bone density, more energy was required to remove the miniscrews as the implantation depth increased, indicating higher resistance and less risk of falling out [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the highest buccal and palatal depth is detected between first molar and second molar. Jin et al indicated that regardless of the cortical bone density, more energy was required to remove the miniscrews as the implantation depth increased, indicating higher resistance and less risk of falling out [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have mentioned complications in applications of miniscrews [ 6 , 10 , 11 ]. Lack of initial stability in the bone is one of the main reasons for miniscrew failures.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the highest buccal and palatal depth is detected between rst molar and second molar. Jin et al, indicated that regardless of the cortical bone density, more energy was required to remove the miniscrews as the implantation depth increased, indicating higher resistance and less risk of falling out (10).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have mentioned complications in applications of mini-screws (6,10,11). Lack of initial stability in bone is one of the main reasons for mini-screw failures.…”
Section: Introductionmentioning
confidence: 99%
“…Але стабільність або ступінь рухливості мініімпланту досить субʼєктивний критерій. Відомо, що на первинну стабільність мініімплантів впливає як щільність кортикальної кістки, так і внутрішньокісткова довжина самого імпланту [59]. І єдине, на що ми можемо орієнтуватись при встановленні мініімпланту -це крутний момент, який не має перевищувати 10 Nсм [55].…”
unclassified